A Critical Investigation of Reader Response in “Howl’s Moving Castle” : A Study of Goodreads Reviews - Aulia Risky Harlina; Nurul Indah Ramadina; Rita Hartati (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Reader response theory offers a dynamic approach to understanding literary interpretation, shifting focus from text-centered analysis to reader engagement. This study investigates reader responses to Diana Wynne Jones's